Organization theory - Hatch, Mary Jo (Oxford University Press, 1997)
Lively and clearly written, this comprehensive and innovative work provides a multi-disciplinary and contemporary introduction to organization theory. Offering an even-handed, balanced appreciation of different perspectives, its approach is pluralist, reflecting the diverse nature of organizational theory as a field of study influenced by thinkers from a variety of disciplines. Readers are encouraged to `adopt' these perspectives to expand their own views on the subject and to enhance their understanding. This book also introduces the multi-perspective approach, explores the ways in which organizations are analyzed, and covers topics of central importance in organizational theory, including decision-making, power, conflict, control, and change within organizations